If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -3(3 + -3x) = 0 2 + (3 * -3 + -3x * -3) = 0 2 + (-9 + 9x) = 0 Combine like terms: 2 + -9 = -7 -7 + 9x = 0 Solving -7 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 9x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 9x = 0 + 7 9x = 0 + 7 Combine like terms: 0 + 7 = 7 9x = 7 Divide each side by '9'. x = 0.7777777778 Simplifying x = 0.7777777778
| 2x-4=10-92 | | 5x+35=14x-73 | | Love=243 | | 8y+7=28 | | 3x-4=2x+10 | | x*0,30=1044 | | x*30=1044 | | (6x^2-31x+5)(x-5)=0 | | 17*x=559 | | 18*x=559 | | 20*x=559 | | 4a-6=a+6 | | 4a-6=a+5 | | 20x=559 | | 4a-6=a+4 | | 4a-6=2a+4 | | 24*x=559 | | 5a-7=2a+5 | | 25*x=559 | | 5(a-6)=a+6 | | 5(a-2)=a+8 | | 5(a-2)=6 | | 9-3(5x+2)=7 | | 5(a-2)=a | | 5(-a-2)=a+6 | | 5(a-2)=-a+6 | | 5(a-2)=_a+6 | | 5(a+2)=a+6 | | 5(a-2)=a-6 | | -5(a-2)=a+6 | | 5(a-2)=a+6 | | 10x+2x=15 |